Nie zaprzepaścić bogactwa młodości. - Brzeziński, Mirosław (Poznańskie Studia Teologiczne, 2020)
The wealth of youth is the wording used by John Paul II in the Letter to the young Parati semper to show that the time of youth is a special period of life which is the wealth of the person who experi- ences it. Also, Francis and the final document of the 2018 Youth Synod show the time of youth as a special period in human life. In the article, based on the teachings of John Paul II, addressed to young people, as well as a post-synodal document for the Young, faith and discernment of vocation, the period of youth is shown as a special time of discovering, getting to know oneself and surrounding reality, designing life. Important elements of the wealth of youth are love, which demands, freedom in truth and friendship with Christ, who helps us discover and realize these values. The article also shows the dangers of the modern world that can interfere with the use of the wealth of youth. They are: culture of temporality, lack of dreams and anxiety, digital environment, excessive and falsified focus on human sexuality, or external living conditions such as armed conflicts, poverty, and various forms of violence. In the face of these threats, ways of preventing and opposing them were also indicated. These are: the choice of Christ as Lord and Friend and openness to His teachings, openness to other people and entering into dialogue with him, it is the pursuit of dreams, shaping and development of spirituality, solidarity and joy of life.